2009
DOI: 10.1128/jcm.01071-09
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae DNA Load in Blood as a Marker of Infection in Patients with Community-Acquired Pneumonia

Abstract: Direct detection of Streptococcus pneumoniae DNA in blood adds to culture results in the etiological diagnosis of patients with community-acquired pneumonia (CAP). Quantification of the amount of DNA, the bacterial DNA load (BDL), provides a measurement of DNAemia that may increase the understanding of the clinical relevance of S. pneumoniae DNA in blood. We evaluated the S. pneumoniae BDL as a diagnostic tool in adult patients with CAP. The BDL was determined in whole-blood samples collected simultaneously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
6
47
0
1
Order By: Relevance
“…We could not correlate DBL with mortality because none of our children died. Our data are in accordance with previous reports showing a relationship between DBL and worse outcome [34,10 ] and prolonged length of hospital stay [9] in patients with severe pneumococcal infections such as pneumonia and meningitis; as well as occurred in patients with meningococcal meningitis in whom there was an association between bacterial load and mortality, complications, sequelae and length of hospital stay [35].…”
Section: P=04)supporting
confidence: 82%
See 1 more Smart Citation
“…We could not correlate DBL with mortality because none of our children died. Our data are in accordance with previous reports showing a relationship between DBL and worse outcome [34,10 ] and prolonged length of hospital stay [9] in patients with severe pneumococcal infections such as pneumonia and meningitis; as well as occurred in patients with meningococcal meningitis in whom there was an association between bacterial load and mortality, complications, sequelae and length of hospital stay [35].…”
Section: P=04)supporting
confidence: 82%
“…Moreover, Real-Time PCR may allow determining the quantification of pneumococcal DNA bacterial load (DBL) in different clinical samples and improving the management of patients with IPD as occur in some viral infections [9,10]. To our knowledge there are no reports about plasma and pleural fluid DBL in children with pneumonia and empyema.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, in another study, a weak or no correlation was observed between circulating HIV-1 RNA and IL-6 levels, indicating that viral load is not a major driver of IL-6 in chronic HIV-1 disease (15). In contrast, in Streptococcus pneumoniae bacteremia patients, a significant moderate-strong correlation was observed between bacterial DNA load and CRP levels (16). In this context, however, it has to be noted that CRP is a protein specifically discovered as a substance present in acute-phase sera from pneumonia patients reacting with pneumococcal C-polysaccharide (17).…”
Section: Discussionmentioning
confidence: 80%
“…S. pneumoniae is the leading cause of CAP worldwide, but a highly sensitive and specific detection method is still lacking. A positive blood culture provides a definite diagnosis, and therefore, several studies have investigated the role of S. pneumoniae PCR on blood samples in the diagnosis of pneumococcal pneumonia (2,23,27,29). In comparison with blood cultures, the use of S. pneumoniae PCR leads to increased sensitivity, since antimicrobial treatment prior to the drawing of the blood sample has little or no influence on the positivity rate.…”
Section: Discussionmentioning
confidence: 99%